Ciência e espiritualidade: conversas com pacientes terminais - Silva, Maria Tereza Penha de Araújo (2008)
It has been reflected on Science and spirituality having as focus the relation between them and the process lived by terminal patients after the confirmation of the finitude of their lives. It has searched with this research to excite discussions that corroborate the tematization of a possible dialogue between science and spirituality, signaling perspectives of debates and formation of an understanding of the problematic that involves these human constructs in the development of alternatives for the understanding of the life finitude. We point out the moment of split between science and spirituality through the cartesian paradigm from a historical approach and after focusing the illness and death as foundation for our discussion. We use as methodological strategy, focal talks with terminal patients having as guidance a guideline with five punctuations: the singular citizen, diagnosis impacts, indicators of science, spirituality marks and death fear that served of base for analysis and data interpretation in according to selected theoretical foundations. Thus, it was possible to perceive that science, although not to keep an explicit dialogue with spirituality, it has pointed through is representation forms to the process indicatives that will culminate with the death. And these indicators had shown that in this direction it is efficient. We believe that the confrontation of the death can happen through of a new science that dialogues with the spirituality, where does not have separation between reason and emotion on the part of science; as well as it does not have reason disdain on the part of the spirituality